The Impact of Digital Marketing and Data Utilization on the Consumer Buying Decision: A Study of the Retail Sector in Canada - Nowrid Amin, Kazi (Digital Repository of Theses, 2026)
This study provides a comprehensive analysis of the impact of digital marketing strategies and data utilization on consumer buying decisions in the Canadian retail sector. The study provides research questions which are What digital marketing and data utilization practices are commonly employed by retailers in Canada? What role does digital marketing play in the consumer purchasing decision-making in the Canadian retail market? What challenges and opportunities do retailers face in using data-driven digital marketing to influence consumer buying behaviour in Canada? What are the suggestions that can be made to retail organizations to enhance consumer purchasing behaviour using digital marketing in Canada? The current research undertakings use an exploratory research study which is backed by a quantitative research design to investigate the influence of digital marketing and data use on consumer purchases in the Canadian retail industry. Moreover, a purposive sampling approach is applied in order to obtain respondents with experience and exposure related to digital retail platforms. There are three cities namely, Toronto, Surrey and Vancouver taken for survey. Therefore, Toronto, Surrey and Vancouver are universe for current research. Sample size for the study includes 600 customers buying products from Canadian retail sectors. Total Population of customers found to be: 4,26,228. The findings of the study establishes that digital marketing, when combined with strategic data utilization, substantially influences consumer buying behaviour in the Canadian retail sector. Younger, educated, and technologically adept consumers are most responsive to personalized campaigns, social media engagement, and omnichannel retail experiences. Retailers that leverage predictive analytics, CRM systems, and ethical data practices are better positioned to enhance customer targeting, optimize promotions, and foster loyalty. Overall, this research underscores the synergistic effect of digital marketing and data-driven strategies, offering significant managerial, operational, and policy implications. The findings provide a strong foundation for future research and practical applications, highlighting the transformative potential of digital marketing in shaping consumer behaviour in an increasingly dynamic retail environment. Keywords: consumer buying behaviour, Canadian retail sector, digital marketing, data utilization and strategies